Relationship among the Financial Problems of Journalists and their Ethical Practices: A Case Study of Faisalabad: Financial Problems of Journalists and their Ethical Practices - Hussain, Dr. Sajid Hussain (Journal of Peace, Development and Communication, 2022)
The fourth pillar of the state is journalism and a responsible press. Journalists must be truthful, accountable, objective, and ethical in their reporting practices and professional duties. However, it is suggested by political economy of media that economic and political elites use media for their interests and benefits. Working journalists are mostly exploited by politicians and owners. Journalists are not well paid and they are enforced to do unethical practices. The objective of present study were to explore the journalist’s economic issues at Faisalabad, and their relationship with ethical practices of journalists. Data was collected through in-depth interviews of 13 working journalists of Faisalabad city. Findings revealed that journalists are facing serious economic issues and these issues are leading them towards unethical practices. Findings imply that government, judiciary and journalistic bodies should play an effective role for overcoming this alarming situation. Keywords: Local journalism, journalists issues, economic pressures, ethical journalism, Gujranwala journalism, political-economy of media.